Global research trends on lifelong learning framework in posthuman education: A bibliometric approach - Haiyan, Hu; Nitiasih, Putu Kerti; Riastini, Putu Nanci; Mahayanti, Ni Wayan Surya (Edelweiss Applied Science and Technology, 2025)
The present study investigates international research trends regarding lifelong learning frameworks through bibliometric methods. This study examines academic publications indexed in the Dimensions database between 2014 and 2024 to determine major trends, significant works, and networks of collaboration that define the discussion on lifelong learning. The study shows a clear upward trend in research output over the last decade, with an impressive increase in studies on digital literacy, micro-credentials, and policy-oriented approaches to lifelong learning. As expected, education systems, curriculum, and pedagogy appear as two of the most prominent research categories, suggesting an overemphasis on practical implementation approaches. However, gaps remain in more granular issues such as education policy or the socio-cultural aspects of lifelong learning. Although providing important insights, this study has limitations. Its dependence on the Dimensions database may not capture relevant literature indexed in other databases like Scopus or Web of Science. Furthermore, limiting articles exclusively to open access may have restricted the breadth of analysis, possibly missing vital findings published in subscription-based journals. We encourage future research to incorporate multiple databases and non-open access literature for a more comprehensive investigation. In addition to bibliometric analysis, interdisciplinary qualitative methods such as expert interviews and case studies are recommended to better understand the motivations behind research and collaboration dynamics. This approach would allow greater attention to policy implications and comparative analyses of different education systems. Addressing these knowledge gaps will help provide a more comprehensive view that will be valuable for researchers, policymakers, and educators as they strive to develop appropriate lifelong learning initiatives. This study underscores the growing importance of lifelong learning as a tool to address challenges in education worldwide and calls for additional interdisciplinary and inclusive research initiatives to shape the future of education.